2013
DOI: 10.4269/ajtmh.13-0315
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Seven Sexually Transmitted Agents in Human Immunodeficiency Virus–Infected Brazilian Women by Multiplex Polymerase Chain Reaction

Abstract: Abstract. We determined the prevalence of seven clinically important pathogens that cause sexually transmitted infections (STIs) (Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium, Trichomonas vaginalis, herpes simplex virus 1 [HSV-1], HSV-2, and Treponema pallidum), by using a multiplex polymerase chain reaction (M-PCR) in samples from Brazilian woman infected with human immunodeficiency virus 1 (HIV-1) and uninfected Brazilian women (controls). The M-PCR assay identified all STIs tested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…The multiplex PCR technique was used for the simultaneous diagnosis of 7 genital infections, which included Chlamydia trachomatis , Herpes virus simplex 1 and 2 (HSV1 and HSV2), Neisseria gonorrhoeae , Mycoplasma hominis , Trichomonas vaginalis , and Treponema pallidum . This was done according to the technique described by Souza et al…”
Section: Methodsmentioning
confidence: 99%
“…The multiplex PCR technique was used for the simultaneous diagnosis of 7 genital infections, which included Chlamydia trachomatis , Herpes virus simplex 1 and 2 (HSV1 and HSV2), Neisseria gonorrhoeae , Mycoplasma hominis , Trichomonas vaginalis , and Treponema pallidum . This was done according to the technique described by Souza et al…”
Section: Methodsmentioning
confidence: 99%
“…From the Brazilian studies that used NAATs, almost all of them were from samples collected by professionals, and the indices varied between 3.2% and 31.8% of prevalence, in several groups of women (pregnant, HIV-positive, women in gynecological consultation of routine, etc.) [9,[22][23][24][25][26]. When the wet mount or culture test was administered, the prevalence found in the Brazilian studies varied between 4.1% and 16% [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…consuming subsequent electrophoresis to detect PCR products (for example [35][36][37][38][39] We sought to determine the rate of T. pallidum, HSV-1/2 and H. ducreyi in ulcers of our patients from Zurich, Switzerland and Graz, Austria. The proportion of 53% of T. pallidum-positive patients in the present study appeared higher than the rates of ulcers caused by syphilis reported from other European areas, for example 2% in the UK [33], 3% in The Netherlands [3] or 35% in France [1].…”
Section: Accepted Articlementioning
confidence: 99%